Methoxychlor enhances degranulation of murine mast cells by regulating FcεRI-mediated signal transduction. (24th November 2014) - Yasunaga, Sho; Nishi, Kosuke; Nishimoto, Sogo; Sugahara, Takuya
Abstract: Methoxychlor, an organochlorine insecticide developed to replace DDT (dichlorodiphenyltrichloroethane), has been reported to induce mast cell degranulation and to enhance IgE-mediated allergic responses. However, the mechanisms underlying these effects are not clear. To clarify potential mechanisms, the effects of methoxychlor on degranulation of mast cells were examined. Degranulation responses were evaluated using RBL-2H3 cells and mouse bone marrow-derived mast cells with either the antigen-induced or calcium ionophore-induced stimulation. Phosphorylation of enzymes related to signaling events associated with mast cell degranulation was analyzed by immunoblotting. Effects on vascular permeability in the passive cutaneous anaphylaxis reaction were evaluated following oral administration of methoxychlor to BALB/c mice. The results indicated that methoxychlor caused increased mast cell degranulation in the presence of antigen, whereas it had no effect on calcium ionophore-induced degranulation of RBL-2H3 cells. Immunoblot analyses demonstrated that the phosphorylation level of phosphoinositide 3-kinase (which plays a central role in mast cell signaling) was increased by methoxychlor during antigen-induced degranulation. In addition, methoxychlor activated the signaling pathway via the high-affinity IgE receptor by inducing phosphorylation of Syk and PLCγ1/2, which transfer the signal for degranulation downstream. Lastly, oral administration of methoxychlor exhibited a tendency to promote vascular permeability in passive cutaneous anaphylaxis model mice. Taken together, the results here suggested that methoxychlor enhanced degranulation through Fcε RI-mediated signaling and promoted allergenic symptoms involved in mast cell degranulation.